Implikasi Hukum Blanko Akta Ppat Setelah Di Keluarkannya Peraturan Kepala Badan Pertanahan Nasional (Perkaban) Nomor 8 Tahun 2012 - Dian Eka Nurul Wardani; Gatot Dwi Hendro Wibowo; Sahnan - (Jatiswara, 2017)
The PPAT deed is one of the main sources for the maintenance of land registration in Indonesia, which serves to ensure legal certainty of the occurrence of a legal act of transition and the imposition of the Mortgage Rights. The purpose of this study is to analyze the legal implications of PPAT form deed after the enactment of Regulation of the Head of National Land Agency (Agreement) No. 8 of 2012. This research is Normative legal research. This study used a statutory approach, conceptual approach and sociological approach. Technique of collecting legal materials through literature study after that done the processing of legal materials with logical and systematic reasoning and analyzed descriptively qualitative and draw deductive conclusions. Based on the result of research of inconsistency in arranging the form of PPAT deed after the issuance of Regulation of Head of National Land Agency (Agreement) Number 8 Year 2012 and its solution if the rules Regulation of Head of National Land Agency (Agreement) Number 8 Year 2012 which is not in accordance with its application. The existence of Regulation of Head of National Land Agency Number 8 Year 2012 About Amendment of Regulation of State Minister of Agrarian / Head of National Land Agency Number 3 Year 1997 About Regulation of Implementation of Government Regulation Number 24 Year 1997 About Land Registration hierarchically higher position than circular letter. In accordance with the principle of lex superior derogat legi inferior which means higher regulation put aside the low (hierarchy principle) and solution Circular letter issued after Regulation of Head of National Land Agency (Agreement) Number 8 Year 2012 must be revoked / withdrawn.